Improving the Local Economy Through Diversifying the Use of Mangrove Forests as Marine Resources - Lukum, Amir; Mahdalena, Mahdalena; Bokiu, Zulkifli (Jambura Science of Management, 2025)
Purpose: This research aims to 1) Analysis of the economic infrastructure around the mangrove forest on the local economy; 2) Identify potential and opportunities for diversification of mangrove forest use; 3) Development of optimal action plans including production, marketing, and sustainability strategy planning. The research was conducted in East Pentadu and West Pentadu Villages, Boalemo Regency, which is one of the mangrove forest locations in Boalemo Regency, Gorontalo Province.Design/Methodology/Approach: The research uses qualitative methods to analyze economic improvement through diversification of mangrove forest use. Data collection and data analysis techniques are carried out through observation and documentation with stages of data reduction, data presentation, and conclusion.Findings: The research results showed that the development of tourist attractions in East Pentadu Village by utilizing the mangrove forest area began in 2017 and West Pentadu in 2022 offers great potential for local economic development. With the background of the beach location in East Pentadu Village which used to be a place for mooring fishing boats and the beach in West Pentadu Village which was not used, these two locations have been transformed into attractive destinations for visitors, both from inside and outside Boalemo Regency. Regarding the use of mangroves in overcoming the problem of managing tourist attractions, several steps need to be taken by the village government and community including forming working groups and dialogue between elements of society.